H2 production from formic acid over highly stable and efficient Cu-Fe-O spinel based photocatalysts under flow, visible-light and at room temperature conditions. (April 2023) - Abdelli, Hanen; Hamoud, Houeida Issa; Bolletta, Juan Pablo; Paecklar, Arnold; Bardaoui, Afrah; Kostov, Krassimir L.; Szaniawska, Ewelina; Maignan, Antoine; Martin, Christine; El-Roz, Mohamad
Highlights: The CuFe2 O4 -based photocatalyst was investigated during FAc dehydrogenation at RT. The Cu/Fe ratio and thermal treatment are investigated during this reaction. Cu:Fe 1:2 treated at 800 °C exhibits the highest activity and good selectivity. An in-situ restructuring of Cu 2+ into Cu +/0 is proposed during FAc photoreforming. Abstract: Catalytic dehydrogenation of liquid organic hydrogen carriers (LOHC), such as formic acid (FAc), is considered as a promising approach to safely store and easily transport hydrogen at ambient conditions. Generally, this process suffers from low activity, low reaction selectivity, low stability of the catalysts and/or the use of noble-metal based catalysts. In this study, a highly efficient CuFe2 O4 -based photocatalyst is reported for the photocatalytic dehydrogenation of FAc under visible light at room temperature and under continuous gas flow. The effects of various factors such as composition of the catalysts and thermal pretreatment are investigated along a series of samples. The synthesis, dispersion, oxidation states, photo-electrochemical properties and performances of these materials were investigated in details. A synergetic effect, with relatively high dehydrogenation selectivity (77% with 6.6 mmol.g −1 . h −1 of H2 production) is obtained on the copper-rich samples without any significant deactivation for two cycles of 20 h/cycle. This study opens up a new route to design new Cu-based photocatalysts as cost-effective materials for visible-light driven photocatalytic dehydrogenation of FAc at room temperature. Graphical abstract: Image, graphical abstract